Neurospora : genomics and molecular biology - Kasbekar, Durgadas Prabhakar; McCluskey, Kevin (Caister Academic Press, 2013)
In this book, internationally recognised Neurospora experts critically review the most important research and demonstrate the breadth of applications to industrial biology, biofuels, agriculture, and human health. The opening chapter is an introduction to the organism. Following chapters cover topics such as: carotenoid biosynthesis, polysaccharide deconstruction, genome biology, genome recombination, gene regulation, signal transduction, self-recognition, development, circadian rhythms and mutation. The book closes with a fascinating look at the history and future trends for research on Neuro.